Zoneamento integrado urbano-ambiental como instrumento jurídico de planejamento para o desenvolvimento sustentável da zona costeira do litoral norte do Rio Grande do Sul - Almeida, Juliana Cainelli de (My University, 2025)
The thesis research aims to establish the systematization of an integrated urban-environmental zoning as a legal instrument for territorial planning and environmental preservation, directing it towards the sustainable development of the coastal zone. As a form of application of the theoretical analysis, the study focuses on the territorial space called the Urban Agglomeration of the Northern Coast of Rio Grande do Sul, through the creation of specific state legislation. It analyzes the creation, definition, and specific characteristics of urban agglomerations with the goal of municipalities joining political and organizational forces to improve specific regional issues. The objective of the thesis is the systematization of an integrated urban-environmental zoning, common to a region, as a legal instrument for territorial planning that promotes sustainable development through geotechnological identification and spatialization. Thus, to carry out urban-environmental diagnosis and prognosis, territorial geoprocessing with identification of areas, technological instrumentation, environmental protection, and qualification of territorial planning, aiming to accelerate regional potentialities, qualify public policies, improve municipal management, and impact quality of life, in order to generate legal security, impartial technique, integrated planning, and sustainability. The framework is based on zoning concepts - which is the instrument for territorial organization and planning - guided by environmental rationality as the driver of decision-making in said planning. The methodology is based on analytical-hermeneutic research as the approach method, through the analysis of theoretical bases interpreted globally, applied to the specific case. Regarding the procedure method, it uses the quanti-qualitative approach, by collecting and handling numerical data and indicators, especially for characterizing the mapping of areas that compose the object, and the qualitative approach, by enabling the identification and analysis of collected data and information, aiming at the composition of the diagnosis and the legislative proposal at the end. It is an exploratory descriptive study, which aims to observe, describe, explore, classify, and interpret aspects of facts or phenomena. Documentary references are used, resulting from empirical research of legislation and public policies of the State of Rio Grande do Sul and the municipalities of the Urban Agglomeration of the Northern Coast, and primary legal elements, legislation, and jurisprudence. As main results, the lack of administrative standardization between federative levels and among municipalities is revealed in the precarious organizational structure, arising the need for intelligent and geotechnological public policies. It is noted that the State does not have integrated planning and regional management instruments, there is a lack of effective oversight, and also technical and financial limitations of municipalities. The proposed thesis is effective for decision-making, monitoring the territory for urban planning, environmental management, and risk prevention. The result of the developed research provides a systematic analysis of a specific region and effectively new information on the subject, given the total disorganization of volatile public policies directed at environmental and urban law. The critical point for implementation is the budget restriction and lack of technical training of municipal servers, therefore the possibility of private sector participation would be the solution. The legislative proposal has a replicable character for other regions, a technical-scientific approach, consistent legal foundation, and flexibility for local adaptations. [resumo fornecido pelo autor]
A pesquisa de tese se destina a estabelecer a sistematização de um zoneamento integrado urbano-ambiental como instrumento jurídico de planejamento territorial e preservação ambiental, direcionando-o para o desenvolvimento sustentável da zona costeira. Como forma de aplicação da análise teórica, volta-se o estudo ao espaço territorial denominado Aglomeração Urbana do Litoral Norte do Rio Grande do Sul, através da criação de legislação estadual específica. Analisa-se a criação, definição e características específicas das aglomerações urbanas com o objetivo de que os municípios juntem forças políticas e organizacionais para o melhoramento de questões específicas da região. O objetivo desta tese é sistematizar um zoneamento integrado urbano-ambiental, aplicável a uma região específica, como instrumento jurídico de planejamento territorial que promova o desenvolvimento sustentável por meio da identificação e espacialização geotecnológica. Assim, realizar o diagnóstico e prognóstico urbano-ambiental, o geoprocessamento territorial com identificação das áreas, a instrumentalização tecnológica, a proteção ambiental e a qualificação do planejamento territorial, visando acelerar as potencialidades regionais, qualificar as políticas públicas, melhorar a gestão municipal e impactar a qualidade de vida, de modo a gerar a segurança jurídica, a técnica imparcial, o planejamento integrado e a sustentabilidade. O referencial tem base nos conceitos de zoneamento - que é o instrumento para a organização e planejamento do território - pautado na racionalidade ambiental como condutora das tomadas de decisões do referido planejamento. A metodologia pauta-se na pesquisa analítica-hermenêutica como método de abordagem, através da análise das bases teóricas interpretadas de forma global, aplicadas ao caso específico. Quanto ao método de procedimento, utiliza-se o quantiqualitativo, por levantar e manusear dados e indicadores numéricos, especialmente para a caracterização do mapeamento das áreas que compõe o objeto, e o qualitativo, por possibilitar a identificação e análise dos dados e das informações coletadas, visando à composição do diagnóstico e à proposta legislativa ao final. Trata-se de um estudo exploratório descritivo, que tem por objetivo observar, descrever, explorar, classificar e interpretar aspectos de fatos ou fenômenos. Utilizam-se referências documentais, fruto da pesquisa empírica da legislação e das políticas públicas do Estado do Rio Grande do Sul e dos municípios da Aglomeração Urbana do Litoral Norte, e elementos jurídicos primários, legislação e jurisprudência. Como principais resultados, a falta de padronização administrativa entre os níveis federativos e entre os municípios são revelados na estrutura organizacional precária, surgindo a necessidade de políticas públicas inteligentes e geotecnológicas. Constata-se que o Estado não possui planejamento integrado e instrumentos regionais de gestão, há falta de fiscalização efetiva e também limitações técnicas e financeiras dos municípios. Por outro lado, há crescimento populacional, expansão urbana e conurbação espacial. A tese proposta mostra-se eficaz para a tomada de decisões, ao possibilitar o monitoramento territorial voltado ao planejamento urbano, à gestão ambiental e à prevenção de riscos. O resultado da pesquisa desenvolvida fornece uma análise sistemática e inovadora de uma região específica, diante da desorganização das políticas públicas instáveis relacionadas ao direito ambiental e urbanístico. O ponto crítico para a implementação é a restrição orçamentária e a falta de capacitação técnica dos servidores municipais, portanto a possibilidade de participação do setor privado seria a solução. A proposta legislativa tem caráter replicável para outras regiões, abordagem técnico científica, fundamentação jurídica consistente e flexibilidade para adaptações locais. [resumo fornecido pelo autor]
Keywords: Direito ambiental; Zoneamento; Planejamento urbano; Sustentabilidade; Environmental law; Zoning; City planning; Sustainability